Duration as another measuring device of space: a journey from Naples to Capri. Issue 1 (2nd January 2019) - Iacovou, Popi
ABSTRACT: The way architects observe and interpret space influences the way they design. A conscious practice of observation of space through movement aims at extending the understanding of space from static and singular to transitory and temporal. Through the use of the moving image space can be captured in time, enabling the documentation of its lived experience and addressing qualities of subjectivity and temporality. Aimed at creating links between the built and the lived environment, the moving image is proposed as a tool that allows for the exploration of duration as another dimension of space. The subject is approached through a design-led project From Naples to Capri, a video installation that explores movement as another practice of architecture, and through theoretical investigations around issues of spatial performativity and Bergson's understanding of duration. Filming is explored as a spatial practice that can potentially shift the role of the architect from a distant observer to an active participant of space, a performer who derives knowledge from the experience of place.